A TB Model with Infectivity in Latent Period and Imperfect Treatment - Juan Wang; Sha-Sha Gao; Xue-Zhi Li (Discrete Dynamics in Nature and Society)
An epidemiological model of TB with infectivity in latent period and imperfect treatment is introduced. As presented, sustained oscillations are not possible and the endemic proportions either approach the disease-free equilibrium or an endemic equilibrium. The expanded model that stratified the infectious individuals according to their time-since-infection θ is also carried out. The global asymptotic stability of the infection-free state is established as well as local asymptotic stability of the endemic equilibrium. At the end, numerical simulations are presented to illustrate the results.